2019
DOI: 10.3390/info10100325
|View full text |Cite
|
Sign up to set email alerts
|

Paper-Based Flexible Electrode Using Chemically-Modified Graphene and Functionalized Multiwalled Carbon Nanotube Composites for Electrophysiological Signal Sensing

Abstract: Flexible paper-based physiological sensor electrodes were developed using chemically-modified graphene (CG) and carboxylic-functionalized multiwalled carbon nanotube composites (f@MWCNTs). A solvothermal process with additional treatment was conducted to synthesize CG and f@MWCNTs to make CG-f@MWCNT composites. The composite was sonicated in an appropriate solvent to make a uniform suspension, and then it was drop cast on a nylon membrane in a vacuum filter. A number of batches (0%~35% f@MWCNTs) were prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…In addition, with the vacuum filtration process, carbon-based film having well-controlled configurational factors such as thickness, width, and length can contribute to manufacturing carbon-based wearable devices on paper substrates. Hossain et al reported a paper-based flexible dry-electrode for detecting electrocardiogram (ECG) signals by using a vacuum filtration method and a hybrid composite material composed of chemically modified graphene and carboxylic groups-functionalized short multi-walled carbon nanotubes (CG-f@MWCNTs), as shown in Figure 2 f [ 59 ]. However, this process is limited to those used for filter-paper substrates.…”
Section: Carbon-based Wearable Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, with the vacuum filtration process, carbon-based film having well-controlled configurational factors such as thickness, width, and length can contribute to manufacturing carbon-based wearable devices on paper substrates. Hossain et al reported a paper-based flexible dry-electrode for detecting electrocardiogram (ECG) signals by using a vacuum filtration method and a hybrid composite material composed of chemically modified graphene and carboxylic groups-functionalized short multi-walled carbon nanotubes (CG-f@MWCNTs), as shown in Figure 2 f [ 59 ]. However, this process is limited to those used for filter-paper substrates.…”
Section: Carbon-based Wearable Sensorsmentioning
confidence: 99%
“…Drop-casting and vacuum filtration; ( e ) reduced graphene oxide (rGO) film deposition onto a functionalized polyethylene terephthalate (PET) substrate using drop-casting process (reproduced with permission [ 58 ] copyright 2014, Elsevier). ( f ) Paper-based hybrid chemically modified graphene and carboxylic groups-functionalized short multi-walled carbon nanotube-based dry electrode (CG-f@MWCNTs) for electrophysiological signal sensing (reproduced with permission [ 59 ] copyright 2019, MDPI AG).…”
Section: Figurementioning
confidence: 99%
“…However, integrating conventional electrodes into the neural system of living animals is complicated by the differences in the mechanical properties of biological surfaces compared to glass or metal (Ganesana et al, 2019;Ji et al, 2019;Liu et al, 2019;Peng et al, 2019). As a result, the development of electrophysiological electrodes with appropriate mechanical (flexible and soft) properties, biocompatibility, and high electrical/electrochemical performance has become a promising field of research for monitoring and modulating neural interfaces with soft tissues, especially for implantation (Hong and Lieber, 2019;Hossain et al, 2019;Jayant et al, 2019;Das et al, 2020).…”
Section: In Vivo Monitoring Of Electrophysiological Signalsmentioning
confidence: 99%
“…There are many kinds of substrate materials for flexible dry electrodes, such as carbon-based materials, artificial fabric [ 32 ], papers [ 33 ] and so on. However, natural leather material is rarely used as the substrate.…”
Section: Introductionmentioning
confidence: 99%